Study of isotope effect on dehydrogenation kinetics of Pd based alloys using differential scanning calorimetry. (1st June 2022) - Sharma, Abhishek; Rawat, Deepak; Raut, S.K.; Jat, Ram Avtar; Parida, S.C.
Abstract: Owing to the large hydrogen isotope effect, palladium and palladium based alloy are of great technological importance for their application in separation of hydrogen isotopes. The present study deals with the investigation of isotope effect on hydrogen desorption kinetics of Pd, Pd0.77 Ag0.23 and Pd0.77 Ag0.10 Cu0.13 alloys, using non-isothermal method by employing Differential Scanning Calorimetry (DSC). Pd0.77 Ag0.23 and Pd0.77 Ag0.10 Cu0.13 alloys were prepared by arc melting method and characterised by XRD, TXRF and EDS. Both the alloys are found to have FCC phase similar to Pd lattice. Prior to kinetic measurements, samples were activated by hydriding-dehydriding method. Hydrogen/deuterium desorption kinetic measurements were carried out at four different heating rates (8, 12, 16 and 20 K/min) and Kissinger plots were constructed from peak temperature of DSC curves. Activation energies for hydrogen/deuterium desorption from the corresponding hydride/deuteride were calculated from the slope of Kissinger plot which follows the order; Pd > Pd0.77 Ag0.23  > Pd0.77 Ag0.10 Cu0.13 . Activation energy for deuterium desorption was found to be lower than that of hydrogen desorption and significant isotope effect was observed for the Pd0.77 Ag0.10 Cu0.13 alloy which makes it a favorable candidate material for its application in hydrogen isotope separation, employing self-displacement gas chromatography. Highlights: Pd0.77 Ag0.23 and Pd0.77 Ag0.10 Cu0.13 alloys prepared and characterised. Desorption kinetics of hydrides and deuterides were studied employing DSC. Activation energy of desorption process was calculated using Kissinger plot. Large isotope effect makes Pd–Ag–Cu alloy suitable for hydrogen isotope separation.